2012
DOI: 10.1080/09603107.2012.654909
|View full text |Cite
|
Sign up to set email alerts
|

Dividend signalling and sustainability

Abstract: We examine the 'disappearing dividends' era documented by Fama and French (2001) with respect to the traditional theory of signalling, wherein the positive signal is one of high future cash flows and continued payments. We report several new findings. First, during the disappearing dividends era, dividends vanished not only because they were less frequently initiated-the oft-cited reason-but also because, once initiated, they were less likely to be sustained. Second, we find that although future performance do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
1
8
0
2
Order By: Relevance
“…In particular, a large part of the studies is dedicated to the market value of company after the announcement of the decision to pay out an initial or maiden dividend (Lipson et al, 1998;McCaffrey and Hamill, 2000). This information is usually positively received by investors, which means that it results in an increase in the market value of company, which is in line with the signaling theory (Hobbs and Schneller, 2012). Most research, based on the cumulative abnormal return (CAR), have showed a positive response of capital markets to the information about: a) an initial dividend payout (Lacina and Zhang, 2008;Sare et al, 2014;Goel, 2015); b) an increase in dividend payment (Dasilas and Leventis, 2011;Sare et al, 2014).…”
Section: Figure a Graphical Illustration Of Dividend Policy Theoriesmentioning
confidence: 83%
See 2 more Smart Citations
“…In particular, a large part of the studies is dedicated to the market value of company after the announcement of the decision to pay out an initial or maiden dividend (Lipson et al, 1998;McCaffrey and Hamill, 2000). This information is usually positively received by investors, which means that it results in an increase in the market value of company, which is in line with the signaling theory (Hobbs and Schneller, 2012). Most research, based on the cumulative abnormal return (CAR), have showed a positive response of capital markets to the information about: a) an initial dividend payout (Lacina and Zhang, 2008;Sare et al, 2014;Goel, 2015); b) an increase in dividend payment (Dasilas and Leventis, 2011;Sare et al, 2014).…”
Section: Figure a Graphical Illustration Of Dividend Policy Theoriesmentioning
confidence: 83%
“…However, their results are contradictory. Research conducted by Hobbs and Schneller (2012) showed no differences in the market value of dividend payers and dividend non-payers. In turn, the research by How et al (2011) and Nguyen (2014) indicated that after five years of regular dividend payouts, the average monthly rate of return is higher for dividend companies ISSN 1994ISSN -1749ISSN .…”
Section: Figure a Graphical Illustration Of Dividend Policy Theoriesmentioning
confidence: 92%
See 1 more Smart Citation
“…W szczególności duża część badań jest poświęcona kształtowaniu się kursu rynkowego akcji po ogłoszeniu decyzji o wypłacie dywidendy inicjalnej (initial dividend, maiden dividend), za którą przyjmuje się pierwszą wypłatę z zysku netto na rzecz akcjonariuszy spółki giełdowej przeprowadzoną przez spółkę po pierwszej ofercie publicznej 1 [Lipson, Maquieira, Megginson, 1998, s. 38;McCaffrey, Hamill, 2000, s. 533]. Informacja o wypłacie pierwszej dywidendy jest zwykle pozytywnie odbierana przez inwestorów, co jest zgodne z teorią sygnalizacji [Payne, 2011, s. 149;Hobbs, Schneller, 2012, s. 1395. W okresie okołoogłoszeniowym obserwuje się zazwyczaj wzrost wartości rynkowej spółki.…”
Section: Reakcja Rynku Kapitałowego Na Wypłatę Dywidendy -Przegląd LIunclassified
“…Badania prowadzone z uwzględnieniem długiego horyzontu inwestycyjnego (obejmujące okres do 5 lat) nie dostarczają jednoznacznych wyników dotyczących reakcji rynku kapitałowego na regularne wypłaty dywidendy. Niektóre analizy [Hobbs, Schneller, 2012, s. 1395 nie wykazują różnic w wysokości kursu rynkowego akcji spółek dywidendowych i tych niewypłacających dywidendy. Inne badania wskazują z kolei, że w ciągu 5 lat po zainicjowaniu wypłaty dywidendy średnia miesięczna stopa zwrotu jest wyższa w przypadku spółek dywidendowych [How, Ngo, Verhoeven, 2011, s. 267;Nguyen, 2014, s. 583].…”
Section: Reakcja Rynku Kapitałowego Na Wypłatę Dywidendy -Przegląd LIunclassified